Working Motivation of Medical Staff and Some Related Factors at a General Hospital in the Mekong Delta, Vietnam in the Context of the COVID-19 Pandemic (Bangladesh Journal of Medical Science, 2023)
Objective: The aim of this paper was to describe work motivation of medical staffs and analyze some related factors.Materials and methods: The study was conducted in internal medicine departments of Kien Giang General Hospital on 384 subjects.Results and Discussion: Regarding the work motivation of medical staffs, the percentage of health workers with good motivation at work accounts for a fairly high rate of 72.9%. The highest achievement aspiration score (average 4.03 points versus maximum 5 points) the lowest was the motivation from recognition of achievement (3.76 points on average).The proportion of good comments about management and supervision factors of medical staff were lowest while satisfaction with management regime and remuneration policy is highest (53.4% and 81.2% respectively).In terms of some related factors to the work motivation of medical staff, positive attitude towards the prevention of the COVID-19 epidemic, good work motivation was 82.2% higher than that of the group of employees who werestill afraid of the disease: 69.6% (OR=2.01; p